O direito de ingresso das pessoas com deficiências na Educação Superior: atos e agentes administrativos em tela - Machado, Jairo Maurano (Universidade Federal de São Carlos, 2022)
The admission's right of people with disabilities to Higher Education was recently evidenced by the system of reservation of places, mandatory at the level of education. However, when two candidates with disabilities occur from the registration and will not be accepted, the question arises: what are the institutional ways to guarantee the income right to the population, when it is for? In this scenario, this research aimed to identify and analyze the institutional instruments available to guide the effectiveness of the income of people with disabilities in Higher Education outside a Public Institution in the State of São Paulo. Specifically, it is intended to: a) identify and portray the acts performed by the institution to legitimize the rights of people with disabilities; b) know and discredit the acts performed by the candidate with a disability to fulfill his right to income; c) analyze, based on the data identified, the process of legitimizing the right to income for people with disabilities in Higher Education from a biopsychosocial perspective. The study was determined in two dimensions of analysis: a) candidate students; b) institutional staffs. It is a case study and documental, analytical-critical-descriptive, which uses public and institutional archives, whose contents are treated with the use of specific registration protocols and analyzed from the perspective of Disability Studies. The research reveals materialities inherent to the right to income of people with disabilities in Higher Education and the institutional contributions to legitimize it. The results obtained indicate the need to review two documents guiding two selection processes. In public practice, they do not always reach all candidates and distortions sometimes occur when there is a fear of a conception of disability in the social model.
The joing' right of people with disabilities into Higher Education: administrative acts and agents in the screen frame
El derecho de las personas con discapacidad a ingresar a la Educación Superior: actos administrativos y agentes en la pantella
Keywords: Educação especial; Direito; Políticas de Ações Afirmativas; Sistema de Reserva de Vagas; Educação Superior; Special Education; Law Field; Affirmative Action Policies; Vacancy Reservation System; Higher Education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO